2014
DOI: 10.1098/rsif.2013.1205
|View full text |Cite
|
Sign up to set email alerts
|

Staying sticky: contact self-cleaning of gecko-inspired adhesives

Abstract: The exceptionally adhesive foot of the gecko remains clean in dirty environments by shedding contaminants with each step. Synthetic gecko-inspired adhesives have achieved similar attachment strengths to the gecko on smooth surfaces, but the process of contact self-cleaning has yet to be effectively demonstrated. Here, we present the first gecko-inspired adhesive that has matched both the attachment strength and the contact self-cleaning performance of the gecko's foot on a smooth surface. Contact self-cleaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 46 publications
3
45
0
2
Order By: Relevance
“…A more finely tuned or altogether different attachment mechanism is needed. It is nontrivial to construct a detachable attachment mechanism similar to those seen in [20], [21], let alone at this much smaller scale. However, we predict that once a more elaborate attachment mechanism is developed, the control strategy illustrated in this paper is suitable for direct application.…”
Section: Resultsmentioning
confidence: 96%
“…A more finely tuned or altogether different attachment mechanism is needed. It is nontrivial to construct a detachable attachment mechanism similar to those seen in [20], [21], let alone at this much smaller scale. However, we predict that once a more elaborate attachment mechanism is developed, the control strategy illustrated in this paper is suitable for direct application.…”
Section: Resultsmentioning
confidence: 96%
“…However, change in surface integrity characteristics with varied electrolyte concentration in ECDM need to be studied to understand the influence of electrolyte concentration on the material removal mechanism and resulting machining quality of ECDM. Furthermore, control over the profile of surface wrinkles may lead to novel applications such as self-cleaning surfaces [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To account for this contradiction, Lee & Fearing [87] proposed that the shaking of the particles during the shearing process was the main reason that seta arrays shed most of the particles (figure 6c). Mengü ç et al [9] believed that the particles rolling under the fibre could enhance the self-cleaning property of a fibrillar adhesion system. Moreover, they suggested that the dragging rate and average load are two critical parameters that affect the performance of the self-cleaning process.…”
Section: Self-cleaning Without Watermentioning
confidence: 99%
“…However, soft fibres showed only 55% recovery upon fouling with large particles, as particles prefer to embed readily within the soft polymers (figure 5c-d) and prevent the further self-cleaning of soft polymers. Further, Mengü ç et al [9] designed vertically aligned elastomer microfibres and tested the self-cleaning properties of the biomimetic material after rsif.royalsocietypublishing.org J. R. Soc. Interface 13: 20160300…”
Section: Self-cleaning Without Watermentioning
confidence: 99%
See 1 more Smart Citation